Motor unit number estimation (MUNE): Where are we now?. Issue 8 (August 2018) - de Carvalho, Mamede; Barkhaus, Paul E.; Nandedkar, Sanjeev D.; Swash, Michael
Highlights: Methods to estimate the number of motor unit numbers are important in neurophysiology. Many methods have been developed, all with specific limitations. To understand the science behind MUNE is fundamental for its application. Abstract: Estimation of the number of motor units (MUNE) in specific muscles is important to monitor outcome in progressive neurogenic disorders, with potential application in clinical trials. However, in spite of recent developments to identify the most convenient technique for MUNE, all current methods have individual shortcomings. It is essential to understand the scientific concepts that support MUNE and the many methods already proposed. In particular, the core role of the compound muscle action potential (CMAP) size in the estimation process is undervalued. Operator-dependent variation in CMAP amplitude or area is the main factor underlying MUNE stability. At present, MUNIX, as standardized in many centers, is probably the best accepted method. Future developments should be based on full understanding of the neurophysiological concepts underlying the MUNE calculation, in order to find a quick, well-tolerated, operator-friendly and reliable method to apply more universally in clinical practice.